HUBUNGAN TINGKAT SPIRITUAL DENGAN KUALITAS HIDUP ORANG DENGAN HIV/AIDS (ODHA) - Dewi Sartika Munthe; Nurlela Petra Saragih; Elfrida Nainggolan; Patimah Sari Siregar; Fajar Amanah Ariga; Kristina L Silalahi (Jurnal Keperawatan Priority, 2022)
Transmission of HIV/AIDS occurs through body fluids containing the HIV virus, namely through sexual intercourse, both homosexual and heterosexual, injection needles in narcotics users, blood transfusions, and from HIV-infected mothers to their babies born. The purpose of this study was to determine the relationship between spiritual level and the quality of life of people living with HIV/AIDS (PLWHA) at the Medan Plus Foundation, Medan. The design of this research is quantitative with observational analysis using a cross sectional approach. HIV/AIDS infection has now affected all groups of people, both high-risk groups and the general. The results of the study showed that the number of respondents with a low spiritual level in PLWHA was 16 respondents, all of them with poor quality of life were 15 respondents (68.1%), and 1 respondent had a good quality of life (4.5%). Meanwhile, as many as 6 respondents who have a good spiritual level with a quality of life of PLWHA less than 2 respondents (9.0%), and 4 respondents who have a good quality of life (18.1%). With the results of the Chi-Square analysis obtained p value = 0.015. It can be concluded that there is a significant relationship between spiritual level and quality of life. Spirituality is an important dimension that must be considered in assessing the quality of life because spiritual disturbances will cause severe psychological disorders, including suicidal ideation.